Penyuluhan ISPA Hipertensi dan Pencegahan Merokok dalam Rumah di RW 04 Kelurahan Yudanagara - Salwa Salsabila; Muhammad Defrian Muldani; Najwa Syifa Nabila Putri; Vina Sabrina; Arumdalu Desri Fitri; Fitriani Sri Rahayu; Azka Megistriani Putri; Andy Muharry (STIKES Columbia Asia Medan, 2024)
Cigarettes have become a habit in society and bring negative effects to oneself and those around, one of which is the emergence of various diseases such as heart disease and vascular disorders. The method used in this community empowerment involves Rapid Rural Appraisal (RAA) by conducting physical interventions through several counseling sessions related to smoking issues and non-physical interventions in the form of installing no-smoking banners in homes. This empowerment activity was conducted in RW 04, Yudanagara Village, Cihideung, Tasikmalaya City. The community empowerment activities conducted include outreach and demonstrations as well as the installation of educational banners. The indicators of the success of the outreach are an increase in participants' knowledge through pre-test and post-test by 50% compared to their knowledge level before attending the outreach, as well as the implementation of a herbal drink-making demonstration. The educational banner contains content about the dangers of smoking indoors. The activities carried out were well-planned, and their implementation can be said to have gone smoothly and successfully.